ANALISI FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT JUDGMENT PADA AUDITOR BPK RI - Agnes Novriana Margaret; Surya Rahardja (Diponegoro Journal of Accounting, 2014)
This research aims to examine empirically the effect of several factors to audit judgment taken by auditor BPK RI. These factors are obedience pressure, task complexity, audit expertise, and audit experience. The sample of this research are auditors who worked at AKN VI Badan Pemeriksa Keuangan (BPK) of RI. The sample was conducted by purposive sampling method. Collecting data was conducted by questionnare distributed directly to auditors as much 120 and only 72 questionnare replayed. Data analysis used multiple linear regression method with SPSS 17. The result of this research showed that obedience pressure and task complexity significantly negative affect audit judgment taken by auditor, but audit expertise and audit experience significantly positive affect audit judgment taken by auditor.